Teste da hipótese da curva de Kuznets ambiental para os países do BRICS - Flores, Rousbell Jusselff Gamez (2017)
In the present dissertation a historical rescue of the debate on the relation between economic growth and ecological sustainability was made; it´s Complemented with an empirical analysis using the Environmental Kuznets Curve (EKC) to unveil the relationship between economic growth (GDP per capita) and indicators of sustainability: CO2 emissions (type A models), the per capita ecological footprint (type B models), the total extraction of materials (Type C models) and the adjusted savings (Type D models), in addition, the influence of other factors such as population density, per capita energy use, trade liberalization, land area used in agriculture, methane emissions and emissions of other greenhouse gases such as byproducts of hydrofurocarbon (HFCs), perfluorocarbons (PFCs) and sulfur hexafluoride (SF6). The analysis was done using time series in Ordinary Least Squares for the BRICS Countries (Brazil, Russia, India, China and South Africa) with annual data in the period from 1980 to 2011 except for Russia which for the availability of the data the analysis was made only for the period 1992-2011. According to the results we tested the inverted U-shaped EKC only for Russia and India in Models A and for India in models type C. The N-shaped EKC only has evidence for India in type B models and for South Africa in type D models. In all cases it is concluded that there is a relationship between economic growth and the sustainability indicators used in this research; This relationship establishes that countries are in a stage of economic expansion that causes worsening in the environment and that agreements such as the Quito protocol and environmental laws have not been enough to regulate economic growth oriented to an ecologically sustainable performance of BRICS countries.